2019
DOI: 10.1128/jvi.00623-19
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus nsp11 Antagonizes Type I Interferon Signaling by Targeting IRF9

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is an arterivirus from the Nidovirales order that causes reproductive failure and respiratory disease in pigs and poses a constant threat to the global pig industry. The PRRSV-encoded nonstructural protein 11 (nsp11) is a nidovirus-specific endoribonuclease (NendoU) that is conserved throughout the Arteriviridae and Coronaviridae families. Previously, our research and that of others demonstrated that PRRSV nsp11 inhibits type I interferon (IFN) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…The functions of nsp15 of coronaviruses (nsp11 in arteriviruses), an endoribonuclease encoded by nidoviruses, have received more attention. Previous studies showed that the nsp15 encoded by SARS-CoV [ 32 ], MHV [ 62 , 63 ], PEDV [ 45 ], PDCoV [ 64 ], and the nsp11 encoded by PRRSV [ 65 , 66 ] can antagonize antiviral innate immune responses by utilizing the different mechanisms involved, e.g., by mediating the evasion of viral dsRNA by host for MHV and HCoV-229E [ 62 , 63 ], by suppressing both MAVS and RIG-I expression for PRRSV [ 66 ], by impairing the activation of transcription factor NF-κB for PDCoV [ 64 ], or by inhibiting MAVS-induced apoptosis for SARS-CoV [ 67 ]. PEDV nsp15 of is a 339-residue polypeptide that results from the cleavage of pp1ab at sites 6139 NLQ↓GLE 6144 and 6478 QLQ↓ASE 6483 by the main protease nsp5.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of nsp15 of coronaviruses (nsp11 in arteriviruses), an endoribonuclease encoded by nidoviruses, have received more attention. Previous studies showed that the nsp15 encoded by SARS-CoV [ 32 ], MHV [ 62 , 63 ], PEDV [ 45 ], PDCoV [ 64 ], and the nsp11 encoded by PRRSV [ 65 , 66 ] can antagonize antiviral innate immune responses by utilizing the different mechanisms involved, e.g., by mediating the evasion of viral dsRNA by host for MHV and HCoV-229E [ 62 , 63 ], by suppressing both MAVS and RIG-I expression for PRRSV [ 66 ], by impairing the activation of transcription factor NF-κB for PDCoV [ 64 ], or by inhibiting MAVS-induced apoptosis for SARS-CoV [ 67 ]. PEDV nsp15 of is a 339-residue polypeptide that results from the cleavage of pp1ab at sites 6139 NLQ↓GLE 6144 and 6478 QLQ↓ASE 6483 by the main protease nsp5.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LAGLS3BP may also help in distinguishing samples from disease controls and those from patients with viral infection but not the detailed subgrouping of infections. As for IRF9 , according to COVID-19-related studies, similar with LGALS3BP , this gene is typically expressed in multiple respiratory infection diseases ( Cheon et al, 2013 ; Wang et al, 2019 ). The deficiency in IRF9 is associated with impaired control of multiple viruses ( García-Morato et al, 2019 ), including SARS-CoV-2, building the functional relationship between IRF9 and respiratory viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…The region of 2019-nCoV domain which encodes nsp 11 spans from about 18046-19824bp. It was indicated in countering host innate antiviral response via inhibition of type I interferon (IFN) production using NendoU activity-dependent mechanisms in porcine reproductive syndrome viruses [ 16 ]. The nsp 11 is also associated with pathways such as programmed cell death evasion, mitogen-activated protein kinase signaling, histone-related, cell cycle and DNA replication and the ubiquitin-proteasome through RNA microarray analysis [ 17 - 20 ] and few nsp 11 inhibitors include papain-like proteinase (plPRO) and 3C-like main protease-3CLpro [ 21 ].…”
Section: Discussionmentioning
confidence: 99%